Makna Kehidupan dalam Film Kartun Doraemon - Robingun Suyud El Syam; Ali Imron; Alfan Nurngain (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research seeks to investigate the meaning of life in the cartoon film Doraemon. The research is qualitative with a descriptive design, through descriptive analysis, it can be concluded that there is a meaning to life which can be a lesson for film lovers for those who see it with positive glasses where nothing is immediate in real life, everything requires a process of effort to make something happen. This study has theoretical implications, namely dissecting the plot of the film in detail, then analyzing life lessons where positive things are used as lessons to be emulated, and the negative sides are to be avoided. The practical implication is that this research can be used as a reference for film lovers to provide education to children, which are the positive and negative aspects. The research provides recommendations for academics who wish to study the meaning of life in cartoon films, as well as the need for strict assistance for children in watching television..